All that I want to forget - ʻĪsá, Buthaynah (Hoopoe, an imprint of American University in Cairo Press, 2019)
"Fatima loves poetry and wants to study French literature--both of which are anathema to her strict and conservative much older brother, Saqr. While living under his roof, Fatima's hopes and dreams are scrutinized, mocked, and slowly crushed as she is forced into his narrow vision of the right path. Then Fatima meets Isam, a poet like her; they email love letters to each other and meet in secret. Saqr, however, has other ideas: she is married off to Faris, a complete stranger. He is not the cruel tyrant her brother was, but still she did not choose him. Will she escape her past to live the life of love and poetry she craves?"--Amazon.com